Integration of Qur'anic Values in Mathematics Learning: A Bibliometric Analysis - Lestari, Fitria; Farid, Fajri; Syazali, Muhamad; Putra, Fredi Ganda; Maulidi, Ikhsan; Apriliani, Vina (Program Studi Tadris IPA, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
The integration of Qur'anic values in learning is an increasingly popular field in Education, therefore this research aims to determine the integration of Qur'anic values in Mathematics Learning This research uses a descriptive qualitative method through literature study research techniques. The data obtained based on 12 journal articles analyzed is based on a critical analysis of the available literature (articles based on scientific novelty content from 2017 to 2024 indexed on Google Scholar) data analysis techniques using VOS viewer software version 1.6.16 for graphical bibliometric mapping. Based on the data obtained Research shows the importance of combining Islamic values with mathematics to build character and advance education. Various models are proposed to integrate mathematical concepts from the Quran, such as numbers, relationships, operations, and measurements, in learning. This integration not only improves students' understanding of mathematics, but also creates a well-rounded educational experience. Therefore, it is highly recommended for teachers to teach mathematics by integrating with the values or verses of the Quran. So that students feel that learning mathematics useful for the development of student competencies.